Irreversibility of winter precipitation over the Northeastern Pacific and Western North America against CO2 forcing - Zhenhao Xu; Yu Kosaka; Masaki Toda; Tomoki Iwakiri; Gang Huang; Fei Ji; Ayumu Miyamoto; Weichen Tao (npj Climate and Atmospheric Science)
Abstract Comprehending the resilience of regional hydroclimate in response to CO2 removal is essential for guiding future mitigation and adaptation strategies. Using an ensemble of model simulations forced by idealized CO2 ramp-up followed by ramp-down, here we show that the winter precipitation over the Northeastern Pacific and Western North America (NPWNA) is irreversible even if global warming is reversed back to 2 °C level. This asymmetric change features a tripolar pattern and is tied to Aleutian Low intensification, which is driven by both zonal and meridional gradients of sea surface temperature (SST) anomalies in the tropical central-eastern Pacific. Distinct from the zonal SST gradient—explained by different timescales of surface and subsurface warming and ocean dynamical processes, amplified through the Bjerknes feedback—the meridional SST gradient originates from the southward shift of the intertropical convergence zone, maintained by the wind-evaporation-SST feedback. Our findings suggest that the regional hydrological risks over the NPWNA induced by CO2 ramp-up cannot be fully eliminated by CO2 removal even if the global warming level is restored back.